Laporan Pertama Meloidogyne incognita yang Menginfeksi Tanaman Melon (Cucumis melo L.) pada Media Cocopeat di Bengkulu, Indonesia - Hamidi, Ilmi; Fauzi, Ariffatchur; Djamilah, Djamilah; Zarkani, Agustin; Prastio, Turko (AGRITROPICA : Journal of Agricultural Sciences, 2025)
Cocopeat, a growing medium derived from coconut husk fibers, is valued for its high porosity, strong water retention, and support for healthy root development. However, its physical properties may also provide favorable conditions for plant-parasitic nematodes. This study reports, for the first time, the occurrence of Meloidogyne incognita in melon (Cucumis melo L.) cultivated in cocopeat in Bengkulu, Indonesia, and examines the susceptibility of this medium to infestation. Root samples were purposively collected from six infected plants showing stunted growth, wilting, and root galling. Adult female nematodes were extracted and identified morphologically through perineal pattern analysis. The diagnostic features, such as a tall, narrow dorsal arch, fine striae, and the absence of lateral lines, consistently matched those of M. incognita. Galls of varying sizes were observed in all samples, indicating different infection intensities. This finding suggests that the physical structure of cocopeat may facilitate nematode mobility and persistence across growth stages. The study highlights that cocopeat is not inherently nematode-free despite its agronomic advantages and should be managed through preventive strategies, including substrate sterilization, sanitation, and regular nematode monitoring.